Karakteristik Fisikokimia Tepung Ubi Banggai dan Aplikasinya Dalam Beras Analog - Aini Auliana Amar; Feri Kusnandar; Slamet Budijanto (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2021)
Banggai yam (Dioscorea sp) has many varieties, which is locally cultivated and consumed by people in Banggai, Central Sulawesi. Banggai yam can be processed into flour and applied as an ingre-dient in analogue rice. This study aimed to evaluate the physical and chemical composition, total phenol and antioxidant activity of banggai yam flours, and the physical properties, total phenol and antioxidant activity of their analogue rice. Five varieties of banggai yams (Harum, Banggai, Pasus, Doso, and Penus) were compared. Banggai yam flours were composed of moisture (12.21-12.74%wb), ash (2.18-2.75%db), protein (10.41-11.68%db), fat (1.05-3.38%db), and carbohydrate (83.22-85.77%db). All banggai flours had different color (L, a, and b values) intensities, and contained starch (65.38-68.40% db) with amylose content of 38.96-45.09% (db). The total phenol ranged from 30.48-116.90 mg GAE/ 100 g, and showed antioxidant activity (58.71-89.50% inhibition). The pasting profile varied among five yam flours. The initial pasting temperatures of banggai yam flour were relatively high (82.5-83.7°C). All banggai yam flour increased in viscosity up to a peak and experienced slight viscosity breakdown during the heating phase, as well as showed a setback viscosity during cooling phase. Rice analogue of yam flours made by extrusion technology had a relatively low bulk density (0.47-0.56 g/mL), and required a long cooking time (7-9 minutes). The rice analog had different levels of total phenol and antioxidant activities. The level of total phenol and antioxidant activity of analogue rice from Harum yam showed the highest compared to those other analogue rice.